Genetic nature of eastern wolves: Past, present and future - Kyle, C.J.; Johnson, A.R.; Patterson, B.R.; Wilson, P.J.; Shami, K.; Grewal, S.K.; White, B.N. (Conservation genetics, 2006)
Eastern North American wolves have long been recognized as morphologically distinct from both coyotes and gray wolves. This has led to questions regarding their origins and taxonomic status. Eastern wolves are mainly viewed as: (1) a smaller subspecies of gray wolf (Canis lupus lycaon), potentially the result of historical hybridization between gray wolves (C. lupus) and red wolves (C. rufus), (2) a hybrid, the result of gray wolf (C. lupus) and coyote (C. latrans) interbreeding, or (3) a distinct species, C. lycaon, closely related to the red wolf (C. rufus). Although debate persists, recent molecular studies suggest that the eastern wolf is not a gray wolf subspecies, nor the result of gray wolf/coyote hybridization. Eastern wolves were more likely a distinct species, C. lycaon, prior to the eastward spread of coyotes in the late 1800s. However, contemporary interbreeding exits between C. lycaon to both C. lupus and C. latrans over much of its present range complicating its present taxonomic characterization. While hybridization may be reducing the taxonomic distinctiveness of C. lycaon, it should not necessarily be viewed as negative influence. Hybridization may be enhancing the adaptive potential of eastern wolves, allowing them to more effectively exploit available resources in rapidly changing environments.[PUBLICATION ABSTRACT]